2005
DOI: 10.1371/journal.pbio.0030183
|View full text |Cite
|
Sign up to set email alerts
|

Engineering a Dimeric Caspase-9: A Re-evaluation of the Induced Proximity Model for Caspase Activation

Abstract: Caspases are responsible for the execution of programmed cell death (apoptosis) and must undergo proteolytic activation, in response to apoptotic stimuli, to function. The mechanism of initiator caspase activation has been generalized by the induced proximity model, which is thought to drive dimerization-mediated activation of caspases. The initiator caspase, caspase-9, exists predominantly as a monomer in solution. To examine the induced proximity model, we engineered a constitutively dimeric caspase-9 by rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
101
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(109 citation statements)
references
References 33 publications
6
101
2
Order By: Relevance
“…Caspase-1, however, apparently differs from these two initiator caspases as cleavage of the enzyme leads to large increases in enzyme activity and dimerization. Caspase-9 and DRONC activation have been shown to be enhanced much more by oligomerization than by proteolysis (39,40,46,47). An interpretation of our combined structural, kinetic, and biochemical data can help explain what is different about caspase-1 and why both dimerization and proteolysis are important for activity.…”
Section: Procaspase-1 Zymogen Domain Structurementioning
confidence: 78%
“…Caspase-1, however, apparently differs from these two initiator caspases as cleavage of the enzyme leads to large increases in enzyme activity and dimerization. Caspase-9 and DRONC activation have been shown to be enhanced much more by oligomerization than by proteolysis (39,40,46,47). An interpretation of our combined structural, kinetic, and biochemical data can help explain what is different about caspase-1 and why both dimerization and proteolysis are important for activity.…”
Section: Procaspase-1 Zymogen Domain Structurementioning
confidence: 78%
“…Based on the molecular dimensions of APAF-1, this suggests a side-by-side arrangement of the CED-4 protomers in the heterotetramer, although no information is available on the details. In a recent paper by Chao et al, 32 it was elegantly demonstrated that dimerisation of caspase-9 alone is not sufficient for full activity (compared to APAF-1-activated caspase-9). Instead, an induced conformational Figure 7 Sequences of BH3 peptides used.…”
Section: Discussionmentioning
confidence: 99%
“…11,12,[14][15][16] Furthermore, this dimeric caspase-9 has significantly enhanced activity compared to its monomeric form. 17,18 Interestingly, cleavage at D315 is not essential for caspase-9 activation by the apoptosome or for cleavage of caspase-3. 16,[18][19][20] Active caspase-3 also cleaves caspase-9 at D330 in a feedback loop to remove an XIAP-binding IBM site, thereby alleviating XIAP inhibition of caspase-9 to allow sustained caspase activation.…”
mentioning
confidence: 99%
“…17,18 Interestingly, cleavage at D315 is not essential for caspase-9 activation by the apoptosome or for cleavage of caspase-3. 16,[18][19][20] Active caspase-3 also cleaves caspase-9 at D330 in a feedback loop to remove an XIAP-binding IBM site, thereby alleviating XIAP inhibition of caspase-9 to allow sustained caspase activation. 19 In Drosophila, the caspase-2/-9 homologue DRONC is required for specific developmental cell death pathways and stress-induced apoptosis [21][22][23][24][25] and is activated by the Drosophila Apaf-1 homologue, ARK.…”
mentioning
confidence: 99%